Green Purchase Intention Towards Consumer Tissue: Empirical Evidence from Indonesia - Rahayu, Sri; Vedy, Nabila Kharimah; Gumanti, Miswan (Talent: Journal of Economics and Business, 2024)
Green purchase intention is the desire of consumers to buy environmentally friendly products. Currently, positive attitudes and subjective norms that consumers have can influence consumers' intention to buy green products. This study aims to examine the direct impact of consumer attitude and subjective norm on green purchase intention and the influence of consumer attitude on subjective norm. This research is a quantitative study with a survey of 150 tissue consumers in Indonesia. This study uses Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Based on the findings, consumer attitudes have an impact on green purchase intentions. Therefore, subjective norms have no effect in increasing green purchase intentions. In addition, consumer attitudes have an effect on subjective norms.